Analysis of the Application of Tapping Box as an Effort to Monitor Restaurant Tax Revenue in Sukoharjo Regency - Afifah Mirna Noviyanti; Hanung Triatmoko; Trisninik Ratih Wulandari; Meka Sabilla Salim (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2022)
This study aims at investigating the implementation of Tapping Box to monitor restaurant tax revenue, its effect, and its contribution to the Regional Original Revenue (Pendapatan Asli Daerah/PAD) in Sukoharjo Regency in 2018-2021, as well as the challenges and strategies in applying the Tapping Box to optimize the tax collection. This study was carried out using a descriptive, qualitative method. The data were gathered using interviews, observation, and literature review. The primary data were sourced from interviews while secondary data were obtained from the Regional Employment Agency (Badan Kepegawaian Daerah/BKD) of Sukoharjo Regency. The results of this study have indicated that the BKD of Sukoharjo Regency can realize a very high level of effectiveness. However, the Tapping Box application as an effort to monitor restaurant tax revenue has not been optimal so it has not given a significant contribution to the tax revenue. This study recommends that the BKD of Sukoharjo Regency carry out socialization and development programs, conduct tax gatherings, give rewards and sanctions, and increase the number of officers.